Decentralized reactive power sharing among parallel inverters through inherent dead-time effect - Qi, Yang (2020)
Load power sharing is an important aspect of the parallel-connected voltage source inverters (VSIs). It is widely accepted that the active power sharing accuracy is ensured by the conventional frequency droop control, whereas the reactive power sharing is poor because of mismatched grid impedances. To overcome this challenge, a novel control scheme is proposed in this paper, which utilizes the inherent dead-time effect to improve the reactive power sharing. As compared with most of the existing power-sharing approaches, the proposed control scheme can eliminate the reactive power sharing error in a completely decentralized manner. Moreover, the VSI output current quality can also be improved at the same time. Simulation and experimental results from a typical microgrid prototype are provided for verification.